Innovation In Teaching Writing With Edu-Game Canva : The Effectiveness For Elementary School Students - Syaharani, Juliana; Ganinda, Nurhayati; Lindawati, Rini (PT. Kreasi Karya Majakata, 2024)
The study aimed to evaluate the effectiveness of using Edu Game Canva in Teaching writing skill to elementary school students. The research utilized a pre-experimental design with a one group pretest-posttest format, where one class was selected using convenience sampling as the study subject. Initially, students were given a pretest to assess their baseline writing skills. This was followed by an intervention where Edu game Canva was integrated into the learning process over several weeks. Subsequently , a posttest was conducted to evaluate the Teaching in the students writing abilities. The results revealed a significant enhancement in students writing skill after the intervention, suggesting that Edu game Canva is effective in supporting writing instruction in elementary schools. These findings highlight the potential for broader application of educational technology like Canva, in elementary school curricula, offering a more interactive and engaging approach to learning that can enhance students academic outcomes.